Management of benzodiazepine misuse and dependence - Brett, Jonathan (Aust Prescr, 2015)
There are well-recognised harms from long-term use of benzodiazepines. These include dependency, cognitive decline and falls. It is important to prevent and recognise benzodiazepine dependence. A thorough risk assessment guides optimal management and the necessity for referral. The management of dependence involves either gradual benzodiazepine withdrawal or maintenance treatment. Prescribing interventions, substitution, psychotherapies and pharmacotherapies can all contribute. Unless the patient is elderly, it is helpful to switch to a long-acting benzodiazepine in both withdrawal and maintenance therapy. The dose should be gradually reduced over weeks to lower the risk of seizures. Harms from drugs such as zopiclone and zolpidem are less well characterised. Dependence is managed in the same manner as benzodiazepine dependence.